1970
DOI: 10.1128/am.19.4.598-603.1970
|View full text |Cite
|
Sign up to set email alerts
|

Production of Amylase in Liquid Culture by a Strain of Aspergillus oryzae

Abstract: The effect of different media and p H on the formation of amylase by Aspergillus oryzae EI 212 is described. Depending upon the composition of the medium and growth conditions, the fungus was found to secrete α- or β-amylase, or both. Some of the properties of the partially purified α-amylase were found to be different from α-amylases from other sources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
2

Year Published

1972
1972
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 12 publications
1
5
0
2
Order By: Relevance
“…La actividad enzimática de la α-amilasa de Aspergillus oryzae a pH 5 no presenta una reducción mayor al 5% de actividad en el intervalo de temperatura de 40 -50°C en comparación con el intervalo 50 -60°C donde existe una pérdida del 30% de actividad, según los resultados descritos por Patel et al [15] y Kundu y Das [18].…”
Section: Resultados Y Discusionesunclassified
See 1 more Smart Citation
“…La actividad enzimática de la α-amilasa de Aspergillus oryzae a pH 5 no presenta una reducción mayor al 5% de actividad en el intervalo de temperatura de 40 -50°C en comparación con el intervalo 50 -60°C donde existe una pérdida del 30% de actividad, según los resultados descritos por Patel et al [15] y Kundu y Das [18].…”
Section: Resultados Y Discusionesunclassified
“…De acuerdo a los datos reportados por Patel et al [15] y Kundu -Das [18] para la α-amilasa de Aspergillus oryzae, el pH la actividad de la enzima es 5 a 50°C, que presenta una reducción del 4% de actividad cuando se reduce el pH a 4 y una reducción del 40% actividad a pH 3 para valores de pH ácidos, por el contrario en valores más básicos como pH 6 se observa una reducción del 20% de actividad, a pH 7 una reducción de 55% y a pH 10 no se presenta actividad enzimática.…”
Section: Resultados Y Discusionesunclassified
“…The activation by Cu2+ ions is unique in the case of neutral proteinase of this strain. It is known that Cu2+ inhibits the enzyme activity of many enzymes (19,11,13,14,22). Recently it has been reported that Cu2+ activates the renin-like enzyme from Aspergil- a A 0.5-ml amount of enzyme solution, 0.2 ml of 10-1 M reagent, and 0.3 ml of glass distilled water were mixed together and kept at 30 C for 60 min.…”
Section: Discussionmentioning
confidence: 99%
“…The enzyme α-amylase (EC 3.2.1.1 ) [27] breaks down long-chain saccharides (starch), yielding maltose, glucose, and "limit dextrin" from amylopectin (Equation 4).…”
Section: Equation-3mentioning
confidence: 99%
“…D2886) was tested on three DNA segments produced from the plasmid pZIP-mCMV-RFP-Puro-(V033), isolated from E.coli bacteria, and cut by three restriction enzymes: EcoRI-HF, BamHI-HF, and Nhel-HF. The DNA segments were incubated with a ligase T4 enzyme for 24h at 16 o C with ATP and a buffer, Tris-HCl (procedure described in [27]) in the presence of Cu 2+ and Cu + ions (1% CH3CN), under anaerobic conditions. The resulting DNA, separated by electrophoresis, and compared to the reaction mixture without the enzyme.…”
Section: Pcr (Polymerase Chain Reaction)mentioning
confidence: 99%